An Analysis of Essential Amino Acid Contents of Canistel Fruit (Pouteria campechiana) as A Source of Vegetable Protein in An Effort of Food Diversification - Harun, Andi Ifriany; Sasri, Risya; Diannisa, Nyemas Firda; Puspasari, Yunita (Universitas Pendidikan Mandalika, 2024)
Canistel fruit is a fruit that is not cultivated and is not known to many people because of limited information about this fruit. In the field of biochemistry, analysis of the essential amino acids contained in canistel fruit has never been carried out. The aim of this research is to determine the type and levels of essential amino acids in Canistel fruit as a source of vegetable protein in an effort to diversify food. The sample used was Canistel fruit. The method used was chromatography using UPLC with a C18 column, PDA detector, gradient pump system, and column temperature of 49â°C. 15 types of amino acids were obtained, consisting of 7 essential amino acids and 8 non-essential amino acids. Essential amino acids are L-Fenilalanin (994,64 mg/kg), L- Isoleusin (704,58 mg/kg), L-Valin (876,69 mg/kg), L-Lisin 1.068,36 mg/kg), L- Leusin (1.199,45 mg/kg), L-Treonin (857,16 mg/kg), and LHistidin (421,03 mg/kg)and 8 non-essential amino acid are L-Serin (957,38 mg/kg), L-Asam glutamat (2.137,7 mg/kg), L-Alanin (1.070,01 mg/kg), LArginin (838,15 mg/kg), L-Glisin (1.101,56), L-asam aspartate (1.900,63 mg/kg), L-Tirosin (141,90 mg/kg), and L-Prolin (1.146,84 mg/kg).